FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN TIKET PESAWAT PADA ONLINE TRAVEL AGENT - Sitorus, Purbanuara Parlindungan; Keke, Yulianti; Ruminda, Marthaleina (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The study aims to investigate factors that affect customers’ decision in buying an aircraft ticket by online travel agent. Due to the technological change, especially the use of internet, aircraft companies developed online system for tickets purchasing method. Passengers are able to buy tickets through online. The data of this study was taken from scheduled domestic airline passengers in Java Island especially in four big cities, such as Jakarta, Bandung, Yogyakarta, and Solo. There were 327 passengers as samples. The study was conducted from June to August 2017. Qualitative approach with T test was used as a method. The result shows that price, easiness, and comfort have positive significant impact toward customers’ trust. Price and easy access have positive impact of customers’ decision while comfort does not give significant impact of customers’ decision in the variable of customers’ decision making.